Design of high quality factor inductor on silicon - Tan, Hai Peng. (2008)
The purpose of this project is to introduce an IC inductor of high quality factor performance on silicon substrate using conventional CMOS or BiCMOS technologies. The thesis conducts a comprehensive study on the conventional rectangular spiral inductors for different numbers of turns using both the experimental measurements and numerical simulations. Several numbers of spiral inductors were simulated with different metal widths. An investigation on the widths to maximize the quality factor of an inductor was performed.